2020
DOI: 10.1016/j.jare.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water and sanitation conditions are associated with the risk of malaria among children under five years old in sub-Saharan Africa: A logistic regression model analysis of national survey data

Abstract: Graphical abstractFlowchart of the method to explore the association between the type of WS and malaria infection among children under five years across sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 40 publications
14
39
2
Order By: Relevance
“…These findings so squar aligns with those of Enebeli et al [28] in Abia state south eastern Nigeria. The findings also concurs with the work of Yang et al [13] who in what, to date, could be considered as the most comprehensive study on the association between WASH conditions and malaria prevalence across the Sub-Saharan Africa (SSA), clearly demonstrated that drinking water and sanitation is a risk factor for malaria infection. households have access to portable source of drinking water which proportion is lower than the national (66%) even though slightly higher than the state (43%) figures as reported in a national…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings so squar aligns with those of Enebeli et al [28] in Abia state south eastern Nigeria. The findings also concurs with the work of Yang et al [13] who in what, to date, could be considered as the most comprehensive study on the association between WASH conditions and malaria prevalence across the Sub-Saharan Africa (SSA), clearly demonstrated that drinking water and sanitation is a risk factor for malaria infection. households have access to portable source of drinking water which proportion is lower than the national (66%) even though slightly higher than the state (43%) figures as reported in a national…”
Section: Resultssupporting
confidence: 91%
“…These findings so squarely aligns with those of Enebeli et al [28] in Abia state south eastern Nigeria. The findings also concurs with the work of Yang et al [13] who in what, to date, could be considered as the most comprehensive study on the association H conditions and malaria Saharan Africa (SSA), clearly demonstrated that drinking water and sanitation is a risk factor for malaria Total, 100…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Good hygiene can be universally considered to be one of the simplest and most effective measures to prevent disease transmission [ 77 ]. The current Covid 19 pandemic has changed the sanitary habits of the population, which may have adverse effects on surfaces highly exposed to disinfectants such as chlorine, for example.…”
Section: Impact Of Ecosystems By the Use Of Chlorinementioning
confidence: 99%
“…The ingestion of contaminated water, which is most often caused by poor sanitation and hygiene often results in various waterborne diseases ( Adelodun et al, 2020b ; Pooi and Ng, 2018 ; Nasser, 1994 ). Yang et al (2020) found an association between drinking water and poor sanitation and the risk of disease infections among children (under five years of age) with the poor socioeconomic condition in sub-Saharan Africa. In 2012, 1.8 billion people which is almost 25% of the world population were estimated to consume contaminated water containing viruses, protozoa, and bacteria ( WHO and UNICEF, 2015 ), that have led to various kind of diseases in human especially gastroenteritis ( Bosch et al, 2008 ).…”
Section: Introductionmentioning
confidence: 98%